AMIGAS: A multicity, multicomponent cervical cancer prevention trial among Mexican American women1. Issue 7 (21st December 2012) - Byrd, Theresa L.; Wilson, Katherine M.; Smith, Judith Lee; Coronado, Gloria; Vernon, Sally W.; Fernandez‐Esquer, Maria Eugenia; Thompson, Beti; Ortiz, Melchor; Lairson, David; Fernandez, Maria E.
Abstract BACKGROUND: Considerable efforts have been undertaken in the United States to reduce cervical cancer incidence and mortality by increasing screening; however, disparities in screening rates continue to exist among certain racial and ethnic minority groups. The objective of the current study was to determine the effectiveness of a lay health worker‐delivered intervention—AMIGAS (Ayudando a las Mujeres con Informacion, Guia, y Amor para su Salud [helping women with information, guidance, and love for their health])—to increase Papanicolaou (Pap) test screening among 3 populations of women of Mexican origin. METHODS: Six hundred thirteen women of Mexican origin in 3 treatment sites were randomized among 4 study arms: the full AMIGAS program with a video and a flip chart (n = 151), the AMIGAS program without the video (n = 154), the AMIGAS program without the flip chart (n = 155), and a usual care control group (n = 153). Six months after enrollment, women were surveyed and reported whether or not they had been screened. RESULTS: Women in any of the intervention arms were statistically significantly more likely to report being screened than those in the usual care group in both an intent‐to‐treat analysis and a per‐protocol analysis. In the intent‐to‐treat analysis, 25% of women in the control group and 52% in the full AMIGAS program group reported having had Pap tests (P < .001); in the per‐protocol analysis, the percentages were 29% and 62%, respectively (P < .001). CONCLUSIONS: AMIGAS was effective in increasing Pap test screening among women of Mexican descent when used in a 1‐to‐1 setting. Future research should compare the 1‐on‐1 intervention with the group‐based intervention. Cancer 2013. © 2012 American Cancer Society.